Optimization of plugging high mobility zones in oil sands by injection of oil-in-water emulsion: Experimental and modeling study. (1st December 2019) - Ding, Boxin; Dong, Mingzhe
Highlights: Tests of emulsion injection were conducted to evaluate plugging of high mobility zones in oil sands. Four stages of emulsion plugging process in sandpacks were observed and analyzed. Emulsion properties, slug size and sandpack length have impacts on each stage of emulsion plugging. A model is proposed for designing an optimal emulsion system in oil sands. Abstract: An oil-in-water (O/W) emulsion treatment has shown its potential in improving the conformance in oil sands, yet it is essential to understand how the displacing pressure drop would vary with the character and size of the fluid slug in oil fields. In this study, emulsion injection followed by water flooding was conducted in 15 sandpack tests to evaluate the emulsion plugging process. Four stages of the plugging process were observed and are discussed. Different emulsion properties (emulsion quality, interfacial tension (IFT) and droplet size), sandpack length, and emulsion slug size were assessed as their impacts on each stage of the plugging process. For a specified emulsion slug, the length of the sandpack can influence the time when the pressure drop starts to decline during the extended water injection, thereby changing the plugging process. Enhancing the "Jamin effect" by promoting the emulsion properties (emulsion quality, IFT and droplet size) does not always provide the best option for plug of high mobility zones in the oil sands. Emulsions with a fast plugging ability have short penetration length in the sandpacks under a required pressure gradient, whereas emulsions with a slow plugging ability may not achieve the expected plugging strength. For a sandpack with specified properties, only injection of an optimal emulsion system can achieve a desired plugging strength and depth. To design an optimal emulsion system, this study developed a new mathematical model to simulate the plugging pressure drop by fully incorporating emulsion properties, sandpack properties and emulsion slug size. The simulated results can successfully match the experimental results.